The effect of antipsychotic drugs on nonspecific inflammation markers in the first episode of schizophrenia - Stefanović Vesna; Mihajlović Goran; Nenadović Milutin; Đukić-Dejanović Slavica; Borovčanin Milica; Trajković Goran (Vojnosanitetski Pregled)
Background/Aim. Immune system disorder, including inflammation, takes a significant place when considering still unclear etiology of schizophrenia. The aim of this study was to determine the blood levels of nonspecific inflammation markers in the first episode of schizophrenia and their relation to the therapy response. Methods. In this study we determined the blood levels of nonspecific inflammation markers: white blood cells count (WBC), C-reactive protein (CRP), erythrocytes sedimentation rate (ESR) and the elements of differential white blood cell counts (or the leukocyte formula): granulocytes (Gra), lymphocytes (Lym) and monocytes (Mon), in the first episode of schizofrenia, in 78 patients hospitalized at the Clinic for Psychiatric Disorders “Dr Laza Lazarević” in Belgrade. The levels were measured at admission to the clinic, as well as after 4 weeks of antipsychotic treatment. The Positive and negative syndrome scale for schizophrenia (PANSS) was applied to measure the severity of psychopathology and response to the treatment. Results. During the first episode of schizophrenia, before initiation of antipsychotic treatment, the frequency of abnormal values was high (≥ 25% of the patients) for the following non-specific inflammation markers: WBC, CRP, ESR and Gra, in the leukocyte formula, but dropped after 4 weeks of antipsychotic treatment at the level of high statistical significance for WBC and Gra (p < 0.001). The ESR remained unchanged in as many as 50% of the patients even after 4-week antipsychotic treatment, at the level of statistical significance in the non-responders compared to the responders (p = 0.045). Conclusion. The obtained results indicate that in the first episode of schizophrenia the blood levels of non-specific inflammation markers (WBS, CRP, ESR and Gra from the leukocyte formula) were high in the subpopulation of patients with the tendency towards normalization of inflammation parameters after a 4-week antipsychotic treatment.